Video-induced commenting and language learning in the digital wilds - Vazquez-Calvo, Boris; Zhang, Leticia Tian (My University, 2022)
Language learning in the digital wilds is not totally unaware and off-the-cuff. While the informality of language learning practices in the digital wilds is undoubted, there is also an intention toward learning in some way because “[…] incidental learning is not really incidental. It is at some level a function of intentional, goal directed, meaningful activity” (Lantolf, Thorne, & Poehner, 2015, n.p.). With a combination of an ethnographic perspective and online observation, we will present two cases of language learning in the digital wilds. First, we will look into specific hashtags and videos to learn Korean on TikTok and the comments they induce (Vazquez-Calvo, Marti, & Zhang, in preparation). Second, we will introduce English-Catalan fan translation by which some Catalan-speaking gamers generate valuable content in Catalan while regaining a space of recognition and status for this minoritized language, often underrepresented in the media and cultural landscape (Vazquez-Calvo, 2022). The two cases exemplify consumption- and production-oriented practices of language learning in the digital wilds, with implications regarding language learning affordances and civic engagement via social media and other digital literacies. These implications may affect the way we may want to transfer language learning in the digital wilds into language education.
Proyecto DEFINERS: Digital language learning of junior language teachers (TED2021-129984A-I00), financiado por MCIN/AEI/10.13039/501100011033 y por la Unión Europea NextGenerationEU/PRTR. Proyecto SEGUE: Social Media and Video Games in the Teaching and Learning of Languages of Preservice Teachers (B1-2021_33), financiado for la Universidad de Málaga.
Keywords: Lenguas - Estudio y enseñanza; CALL; Language learning in the digital wilds; Commenting online; Social media